RANCANG BANGUN SISTEM KENDALI OTOMATIS DAN MONITORING SUHU DAN KELEMBAPAN PADA RUMAH BURUNG WALET BERBASIS BLYNK - Arief, Azran Budi (Jurnal Informatika dan Teknik Elektro Terapan, 2024)
Swallow's nest currently has a high economic value. Swallow's nest is made of swallow's saliva in the shape of a bowl. Swallow nests are naturally formed in caves or buildings that are quite humid with dim to dark lighting. This bird's nest is attached to the ceiling which is generally used by swallows as a place to rest and breed. This system uses ESP32 as a microcontroller that will control the mistmaker through a relay module, process and send the reading data from the BME280 sensor to the monitoring system with the blynk application. The type of mistmaker used to control environmental conditions in the swallow house is AUDAX AXH-5500. This system will maintain temperature conditions in the range of 26 - 29 ºC and humidity in the range of 80 - 90% RH. Mistmaker will be turned on if the temperature > 29 ºC or humidity < 80% RH and will be turned off when the temperature < 26 ºC or humidity above 90% RH. The test results of this study are the average temperature in the swallow house during the use of this tool is 28.17 ºC and humidity 84.24% RH.